Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1177/13548565231164759
|View full text |Cite
|
Sign up to set email alerts
|

Know(ing) Infrastructure: The Wayback Machine as object and instrument of digital research

Abstract: From documenting human rights abuses to studying online advertising, web archives are increasingly positioned as critical resources for a broad range of scholarly Internet research agendas. In this article, we reflect on the motivations and methodological challenges of investigating the world’s largest web archive, the Internet Archive’s Wayback Machine (IAWM). Using a mixed methods approach, we report on a pilot project centred around documenting the inner workings of ‘Save Page Now’ (SPN) – an Internet Archi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Special issue contributors discuss and offer approaches to critically reappropriating online devices and digital infrastructures as the 'methods of the media' (Rogers, 2013;Weltevrede, 2016); cf. Ogden et al (2023), Rieder et al (2022), andChao et al (2024) in this special issue), in order to access and assess their 'cascades of inscriptions' (Ruppert et al, 2013), creating awareness for their workings, their glitches, and flaws. This can be done through active and deliberate application of the underlying technologies and infrastructures, including AI and specifically ML techniques (Chávez Heras (2023) and Sánchez Querubín and Niederer (2022) in this issue) as well as through computational tool(-) making (Chao et al (2024) and Rieder et al (2022) in this issue).…”
Section: What Is Technical?mentioning
confidence: 99%
See 2 more Smart Citations
“…Special issue contributors discuss and offer approaches to critically reappropriating online devices and digital infrastructures as the 'methods of the media' (Rogers, 2013;Weltevrede, 2016); cf. Ogden et al (2023), Rieder et al (2022), andChao et al (2024) in this special issue), in order to access and assess their 'cascades of inscriptions' (Ruppert et al, 2013), creating awareness for their workings, their glitches, and flaws. This can be done through active and deliberate application of the underlying technologies and infrastructures, including AI and specifically ML techniques (Chávez Heras (2023) and Sánchez Querubín and Niederer (2022) in this issue) as well as through computational tool(-) making (Chao et al (2024) and Rieder et al (2022) in this issue).…”
Section: What Is Technical?mentioning
confidence: 99%
“…By conducting a ‘feasibility analysis’ of these documents, Pawlicka-Deger (2022) unpacks the social, technical, and management issues that arise in the process of creating digital artefacts within the context of the Digital Humanities, also aiming at offering a methodological framework for the analysis of documents produced in this field and posing questions about the sociotechnical quality of digital production. Ogden et al (2023) paper ‘Know(ing) infrastructure: The Wayback Machine as object and instrument of digital research' reports on a pilot project concerned with documenting the inner-workings of ‘Save Page Now’ (SPN), an Internet Archive tool that allows users to initiate the creation and storage of ‘snapshots’ of web resources. Considering SNP in the context of documenting human rights abuses, the authors engage with the relationship between how digital infrastructures create new knowledge about the world, their implications and the new methodologies needed to understand them for a meaningful interaction.…”
Section: Ctps According To Special Issue Contributorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of Internet archivists has been examined using ethnographic approaches (Ogden, et al, 2017). Quality and veracity of the archival record of the Web has been discussed, highlighting its strengths and limitations (Nguyen and Weber, 2015;Gaffney and Matias, 2018;Ogden, et al, 2023). Murphy, et al (2007) discussed the potential of the Wayback Machine as a tool for investigating validity across the fields of e-commerce, information systems and computer-mediated communication.…”
Section: State Of Researchmentioning
confidence: 99%
“…Web archive criticism has identified the opportunities and limitations of web archives as data (Rogers 2017;Brügger 2018). Studies have shown how web archives are fundamentally shaped by the infrastructures of web archiving (Summers and Punzalan 2017;Ben-David and Amram 2018;Webster 2017;Dougherty and Meyer 2014;Hegarty 2022b;Ogden, Summers, and Walker 2023), the practices that produce web archives (Summers 2020;Ogden, Halford, and Carr 2017) and the 'archivability' of the Web (Kelly et al 2013;Banos and Manolopoulos 2016). This form of source criticism is further complicated by the sociotechnical complexity of web archives (Ben-David and Huurdeman 2014;Brügger 2012;Rogers 2017), often making it difficult for researchers to address the provenance of data (Maemura et al 2018), or trace back the decision-making processes to a single cause.…”
mentioning
confidence: 99%